Analysis of the Effect of Compensation, Organizational Culture, Work Stress on Employee Productivity in the Administration Section of the Environmental Polytechnic of Medan - Febrian Syahputra HR; Rindi Andika; Ocdy Amelia (Rowter Journal, 2022)
This research was conducted to explain the partial or simultaneous influence of compensation variables, organizational culture, and work stress on employee productivity in the environmental administration section of the Medan State Polytechnic. The total population used was 82 respondents consisting of administrative employees working at the Medan State Polytechnic who were taken using a questionnaire which was used as a data collection method in this study.This study uses multiple linear regression analysis. The results of the analysis show that there is a simultaneous significant effect between the three variables, and a partially significant influence between the compensation variable and organizational culture on productivity, and the work stress variable has no effect on employee productivity in the environmental administration section of the Medan State Polytechnic.